New Zealand : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper analyzes the effect of international migration on unemployment in New Zealand. The empirical results in this paper suggest that net migration inflows give rise to a fall in the unemployment rate. The paper estimates a system of equations including the unemployment rate, real wage, net migration rate, and labor force participation rate, taking into account the interdependence of the variables. It also examines the impact of exchange rate volatility on export firms' decisions to hedge foreign exchange exposure.